Progress towards lymphatic filariasis elimination in Ghana from 2000-2016: Analysis of microfilaria prevalence data from 430 communities - Biritwum, Nana Kwadwo; Frempong, Kwadwo K.; Verver, Suzanne; Odoom, Samuel; Alomatu, Bright; Asiedu, Odame; Kontoroupis, Periklis; Yeboah, Abednego; Hervie, Edward Tei; Marfo, Benjamin; Boakye, Daniel A.; de Vlas, Sake J.; et al. (PLOS Neglected Tropical Diseases, 2019)
Author summary Lymphatic filariasis (LF) control in Ghana has relied on ivermectin and albendazole since the year 2000 when the Ghana Filariasis Elimination Programme started. We analyzed trends in microfilaraemia prevalence during MDA, reported coverage, and transmission assessment survey using data obtained from the Ghana Health Services (GHS). The median reported treatment coverage varied between 77–80% over the years. Our results show that the treatment in Ghana made a significant impact in reducing infections <1% in majority of sentinel sites in endemic districts (81/98) by 2016. In the remaining 17 districts, extra efforts may be needed to achieve the same goal. Some of the challenges could be low coverage in some communities, high baseline endemicity, programme logistical challenges etc. The required average rounds of MDA needed to reach mf prevalence < 1% was 11, higher than that proposed by the Global Filariasis Elimination Programme. This article is relevant to LF control programmes in assessing the impact of MDA. It is important for programmes to monitor infections especially within communities where mf prevalence is still above the 1% threshold to ensure that the WHO 2020 target is achieved.